Mysticism in English Literature - Spurgeon, Caroline F. E. (Caroline Frances Eleanor), 1869-1942 (Salt Lake City, UT : Project Gutenberg, 2004)
"Mysticism in English Literature" by Caroline F. E. Spurgeon is a scholarly exploration of the concept of mysticism as it relates to notable English writers, written in the early 20th century. This work seeks to define mysticism, tracing its philosophical roots and examining how it manifests in the works of various poets and prose writers. The book emphasizes the idea that mysticism is not merely a set of beliefs but an experiential attitude that connects the individual with a greater universal truth. The opening of the book lays the groundwork for this exploration by clarifying the term "mysticism" and its often mistaken interpretations. Spurgeon discusses how the concept has evolved from ancient philosophical thought, specifically referencing figures like Plato and Plotinus, to its presence in English literature. She articulates that mysticism represents a conviction of unity underlying all existence, distinguishing between the intellectual understanding and the direct experiential knowledge of this unity. The author begins to outline how leading English writers, including Wordsworth, Blake, and Browning, express mystical thoughts through their works, inviting readers to delve deeper into the interplay between literature and spiritual experience. (This is an automatically generated summary.)
Release date is 2004-04-01
Produced by Distributed Proofreaders
Keywords: English literature -- History and criticism; Mysticism -- Great Britain; Mysticism in literature